Estudo estrutural, morfológico, elétrico e óptico de cristais de a-Ag2WO4 dopados com Mo6+ via co-precipitação assistida por PVP - Silva, André Lima e [UNESP] (2015)
In this study were synthesized Mo6+ doped α-Ag2WO4 microcrystals at concentrations of 0, 0,1, 0,2 0,4 e 0,8% by co-precipitation at 100 ºC in presence of polyvinylpyrrolidone surfactant. Were obtained pale-yellow polycrystalline powders that were characterized by x ray diffraction, MicroRaman spectroscopy, scanning electron microscopy (SEM), photoluminescence spectroscopy and UV/Vis diffuse reflectance. They was indexed as alfa and γ-Ag2WO4 by the crystallographic standards JCPDS 34-0061 and 33-1197, respectively. The Rietveld refinament using ICSD No. 4165 was performed to calculation of lattice parameters and atomic positions. The results revealed a high degree of disorder in short, medium and long range which increases with doping such as a progressive reduction of unit cell volume and cubic phase formation is inducted. Except to 0,1% Mo6+, SEM images showed hexagonal crystals, size about 1 μm, presenting morphological defects such as fractures, irregular surfaces and polyfaced crystals. Further was noted a rapid growth of silver nanoparticles on the surface of these materials during exposure to 10 keV electron beam accelerated in SEM. The samples also showed ohmic behavior with 1.074x1010 Ω·m order resistence, α-Ag2WO4 pure crystals exhibited strong photoluminescence in the red region of eletromagnetic spectra which is reduced by doping, with no significant changing on FT profiles by Mo6+ increasing concentration being noted. The lowest band-gap (3.05 eV) was obtained with 0,8% doped sample.